PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA BADAN KEUANGAN DAERAH (BAKEUDA) KABUPATEN KENDAL - Arganata, Muhammad Faizal; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2017)
The purpose of this research is to analyze the effect of transformational leadership and working motivation on the performance of the workers. In this research, the researcher analyzes the performance of the workers on Financial Management Board of Kendal County by using independent variable, such as transformational leadership and working motivation. This research was conducted on Financial Management Board of Kendal County. Samples were selected by applying Saturated Sampling method (Census Sampling). Data was obtained by directly giving questionnaires to 100 employees of Financial Management Board. The analysis of data used double linear regression method by SPSS (Statistic Product and Service Solution) 16 program.The result of the analysis shows that transformational leadership has positive and significant impacts to the workers’ performance. Researcher suggests to increase more variable and extend the population in the future research.